2014
DOI: 10.1111/anu.12087
|View full text |Cite
|
Sign up to set email alerts
|

Alternative dietary protein sources for Atlantic salmon (Salmo salarL.) effect on intestinal microbiota, intestinal and liver histology and growth

Abstract: The present study has addressed the issue of dietary alterations on gut microbiota in fish by investigating modulation of the allochthonous and autochthonous bacterial gut community of Atlantic salmon following feeding with pea protein concentrate, soy protein concentrate, extracted sunflower, poultry by-product and feather meal. The results revealed that total allochthonous and total autochthonous bacteria isolated from the distal intestine (DI) were affected by dietary modulations. Total autochthonous bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 81 publications
(173 reference statements)
10
106
1
3
Order By: Relevance
“…The decreased activity of C-LAP in the chyme also indicates that the plant ingredients investigated in this trial did not cause inflammation, which has been reported to be accompanied by increased cell turnover and sloughing (Bakke-McKellep et al 2007;Chikwati et al 2013b). The lack of inflammation was also confirmed by the histomorphological evaluation conducted and reported from this feeding trial (Hartviksen et al 2014). Some variable responses were observed by the different plant ingredients on intestinal function.…”
Section: Plant Proteinssupporting
confidence: 76%
See 2 more Smart Citations
“…The decreased activity of C-LAP in the chyme also indicates that the plant ingredients investigated in this trial did not cause inflammation, which has been reported to be accompanied by increased cell turnover and sloughing (Bakke-McKellep et al 2007;Chikwati et al 2013b). The lack of inflammation was also confirmed by the histomorphological evaluation conducted and reported from this feeding trial (Hartviksen et al 2014). Some variable responses were observed by the different plant ingredients on intestinal function.…”
Section: Plant Proteinssupporting
confidence: 76%
“…A compensatory feedback mechanism may be involved to mitigate the loss of function caused by the inflamed DI (see also Bakke-McKellep et al 2000;Krogdahl et al 2003;Chikwati et al 2013a). However, the more refined SPC, which removes most of the unfavorable ANFs and/or other components that cause inflammation (van den Ingh et al 1996;Francis et al 2001), has not been reported to cause overt inflammation in the DI in this (Hartviksen et al 2014) or previous studies (Olli et al 1994;Penn et al 2011). Thus, it is more likely that the reduced BBM-LAP activity in the DI was due to increased digestive and absorptive processes in the proximal part of the GI tract, as indicated by higher BBM-LAP in the PI and increased PI and MI weights (Hartviksen et al 2014), resulting in less substrate present in the DI chyme and thus a down-regulation in tissue enzyme activity.…”
Section: Plant Proteinsmentioning
confidence: 88%
See 1 more Smart Citation
“…Chapter 3 2011; Turnbaugh et al, 2009b;Muegge et al, 2011;Delsuc et al, 2014) and fish Ingerslev et al, 2014;Meziti et al, 2012;Hartviksen et al, 2014). This is not the case in our study where the same feed was used in all treatments.…”
mentioning
confidence: 75%
“…Peptostreptococcaceae is a family of obligate anaerobic bacteria (Ringø et al, 1995). In salmon, Peptostreptococcaceae was detected as a member of both the allochthonous and autochthonous microbiota regardless of the fish diet, indicating that Peptostreptococcaceae might be a natural part of the intestinal microbiota of this species (Hartviksen et al, 2014). The family has been also reported in the gut microbiota of yellow catfish and common carp (van Kessel et al, 2011).…”
mentioning
confidence: 97%